2015
DOI: 10.1089/jir.2014.0083
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Interferon Lambda Against Lymphocytic Choriomeningitis Virus

Abstract: Lambda interferons inhibit replication of many viruses, but their role in the inhibition of lymphocytic choriomeningitis virus (LCMV) infection remains unclear. In this study, we examined the antiviral effects of interferon (IFN)-λ2 and IFN-λ3 against LCMV in A549 cells. We found that IFN-λ2 is a more potent inhibitor of LCMV strain MX compared with IFN-λ3, whereas both cytokines have similar antiviral effects against an immunosuppressive variant of LCMV, clone-13. We also demonstrated that the antiviral activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…We hypothesize that these variations in IFN-induced ISGs contribute to differential levels of NO induction. One such limitation of our study is that we did not verify the expression of IFN receptors on the lung epithelial cells, although these cells are known to respond to the different IFNs (18,77) and express the distinct IFN receptors (75, 78,79).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that these variations in IFN-induced ISGs contribute to differential levels of NO induction. One such limitation of our study is that we did not verify the expression of IFN receptors on the lung epithelial cells, although these cells are known to respond to the different IFNs (18,77) and express the distinct IFN receptors (75, 78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that IFN-λ, being a nonspecific activator of a large group of ISGs, exhibits antiviral activity against a whole group of negative strand ssRNA viruses: IVA [18,21,[33][34][35][36][37][38]; IBV [39]; RSV [2,40,41]; and LCMV [42]. Some positive strand ssRNA viruses are also affected, such as: HCV [14,[43][44][45]; Dengue virus [46,47]; and rhinovirus [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…As a potent antiviral molecule, IFN-λs are capable of a variety of functions against: Hepatitis C virus, 29 Hepatitis B virus, 30 Herpes viruses, [31][32][33][34] Human immunodeficiency virus, 35 Dengue virus, 36 Zika virus, 37 SARS corona virus, 38,39 Influenza virus, 40 human metapneumovirus, 41 Lymphocytic choriomeningitis virus, 42 Norovirus, 43 Rhinovirus, 44 and many others. In addition to viral diseases, IFN-λs have a wide variety of actions in reduction and control of bacterial, fungal, and parasitic infections.…”
Section: Ifn-λs Influence On Medical Diseases and Disordersmentioning
confidence: 99%